Effect of Melatonin on Some Indicators of Vegetative and Biochemical Growth in Washingtonia filifera Trees Under Salinity Stress - Amjad H.K. Hussein; Aqeel H.Abdulwahid; Haider S. S. Al-jabir (University of Thi-Qar Journal of agricultural research, 2024)
The experiment was conducted at the Agricultural Research Station of the College of Agriculture, University of Basrah, during the 2023-2024 growing season. The objective was to study the effect of different levels of irrigation water salinity (2, 6, and 12 dS.m-1) and melatonin treatment (0, 50, and 100 mg.L-1) on the vegetative and biochemical growth indicators of Washingtonia filifera seedlings. The experiment was carried out as a factorial experiment with three replicates, following the Randomized Complete Block Design (RCBD). The results were analyzed using the GenStat program, and means were compared using the Least Significant Difference (LSD) test at a 0.05 probability level. The results showed a significant decrease in growth with increasing salinity levels, with the 2 dS.m-1 treatment outperforming in most traits, including plant height, leaf number, leaf area, and chlorophyll and carbohydrate content, and a significant decrease in proline content. Additionally, the results indicated that plants sprayed with 100 mg.L-1 of melatonin outperformed those with other treatments in most of the studied traits. Regarding the interaction effect between the study factors, there was a significant impact on most of the studied traits.